2007
DOI: 10.1210/er.2006-0039
|View full text |Cite
|
Sign up to set email alerts
|

Small for Gestational Age: Short Stature and Beyond

Abstract: Depending on the definitions used, up to 10% of all live-born neonates are small for gestational age (SGA). Although the vast majority of these children show catch-up growth by 2 yr of age, one in 10 does not. It is increasingly recognized that those who are born SGA are at risk of developing metabolic disease later in life. Reduced fetal growth has been shown to be associated with an increased risk of insulin resistance, obesity, cardiovascular disease, and type 2 diabetes mellitus. The majority of pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
376
1
29

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 448 publications
(418 citation statements)
references
References 379 publications
(285 reference statements)
12
376
1
29
Order By: Relevance
“…The thrifty phenotype hypothesis [38] suggests that the fetus adapts to an adverse intrauterine environment by diverting limited nutrients to favor the survival and development of vital organs, such as the brain, at the expense of growth. Important metabolic pathways would be permanently programmed during fetal life, leading to metabolic disturbances in adulthood [31,39]. There is evidence suggesting that the degree of weight gain Finally, elevated plasma FFAs inhibit the insulin signal transduction system [24,113,114].…”
Section: Adipocytokines In Children Born Small For Gestational Agementioning
confidence: 99%
“…The thrifty phenotype hypothesis [38] suggests that the fetus adapts to an adverse intrauterine environment by diverting limited nutrients to favor the survival and development of vital organs, such as the brain, at the expense of growth. Important metabolic pathways would be permanently programmed during fetal life, leading to metabolic disturbances in adulthood [31,39]. There is evidence suggesting that the degree of weight gain Finally, elevated plasma FFAs inhibit the insulin signal transduction system [24,113,114].…”
Section: Adipocytokines In Children Born Small For Gestational Agementioning
confidence: 99%
“…Although this association is clearly established in adults (5), results in children are still conflicting (6). Some authors have suggested that IR, as a consequence of intrauterine growth retardation would be detectable as early as birth (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Although there were important differences in risk factors for diabetes between the two settings, estimates suggest that effect sizes of BMI on HOMA%S were the same in Limache and Ribeirao Preto. Although most studies have shown an effect of BW on HOMA%S, this observation is not unanimous [27]. Gupta et al found higher insulin resistance among Indian low BW children [28] whereas in the UK no association was observed in children [10,11].…”
Section: Interpretation Of the Findingsmentioning
confidence: 98%